Development of a novel imaging agent using peptide-coated gold nanoparticles toward brain glioma stem cell marker CD133. (1st January 2017) - Cho, Jun-Haeng; Kim, A-Ru; Kim, Sang-Heon; Lee, Su-Jae; Chung, Hoeil; Yoon, Moon-Young
Graphical abstract: Abstract: CD133 is known as biomarker for glioblastoma (GBM) and also serves as a marker for cancer stem cells (CSCs), which carry out tumorigenesis and resist conventional therapeutics. The presence of CD133-presenting CSC is a one of the factors in maintenance of the tumorigenic potential of GBM. Thus, CD133 is a potential target for accurate diagnosis of GBM, which could improve its poor prognosis for patients when CSCs are present. Herein we designed a small peptide-based imaging agent with stimulus-responsive properties. A novel small peptide, CBP4, was screened by a phage display technique, and demonstrated binding to the target CD133 (ECD) comparable to that of an antibody. As a quencher, we used gold nanoparticles (GNPs); the targeting peptide was conjugated to GNPs with high efficiency. By means of a quenching effect, the peptide-coated GNP showed 'signal on–off' properties depending upon the presence of the target. In addition, the particles exhibited biocompatibility when localized in the cytosol. Thus, this study demonstrated that the peptide-coated GNPs can be utilized as an imaging agent for accurate diagnosis of GBM, and further as a drug carrier for therapeutic approaches. Statement of Significance: The diagnosis and determination of prognosis made by cancer stem cell markers could be a key strategy to eradicate cancer stem cells and cure the cancer. The significance of this study is the characterization of quenching-based signal on–off mechanism and showed that the active targeting via peptide can contribute to the design of a stimulus-responsive cellular imaging agent. Moreover, small peptide based nano complexation showed specific recognition of the target stem cell and internalized on cellular cyotosol with stimulus responsive fluorescence. With its novel biocompatibility, the strategy might be a promising tool for drug carrier systems able to measure and visualize the delivered efficiency at intracellular sites.